A geochemical study of the Ediacaran discoidal fossil Aspidella preserved in limestones: Implications for its taphonomy and paleoecology. Issue 4 (11th April 2017) - Bykova, N.; Gill, B. C.; Grazhdankin, D.; Rogov, V.; Xiao, S.
Abstract: The Ediacara biota features the rise of macroscopic complex life immediately before the Cambrian explosion. One of the most abundant and widely distributed elements of the Ediacara biota is the discoidal fossil Aspidella, which is interpreted as a subsurface holdfast possibly anchoring a frondose epibenthic organism. It is a morphologically simple fossil preserved mainly in siliciclastic rocks, which are unsuitable for comprehensive stable isotope geochemical analyses to decipher its taphonomy and paleoecology. In this regard, three‐dimensionally preserved Aspidella fossils from upper Ediacaran limestones of the Khatyspyt Formation in the Olenek Uplift of northern Siberia offer a rare opportunity to leverage geochemistry for insights into their taphonomy and paleoecology. To take advantage of this opportunity, we analyzed δ 13 Ccarb, δ 18 Ocarb, δ 13 Corg, δ 34 Spyr, and iron speciation of the Khatyspyt Aspidella fossils and surrounding sediment matrix in order to investigate whether they hosted microbial symbionts, how they were fossilized, and the redox conditions of their ecological environments. Aspidella holdfasts and surrounding sediment matrix show indistinguishable δ 13 Corg values, suggesting they did not host and derive significant amount of nutrients from microbial symbionts such as methanogens, methylotrophs, or sulfide‐oxidizing bacteria. δ 13 Ccarb, δ 18 Ocarb, and δ 34 Spyr data, along with petrographic observations, suggest that microbial sulfate reduction facilitated the preservation of Aspidella by promoting early authigenic calcite cementation in the holdfasts before matrix cementation and sediment compaction. Iron speciation data are equivocal, largely because of the low total iron concentrations. However, consideration of published sulfur isotope and biomarker data suggests that Aspidella likely lived in non‐euxinic waters. It is possible that Aspidella was an opportunistic organism, colonizing the seafloor in large numbers when paleoenvironments were favorable. This study demonstrates that geochemical data of Ediacaran fossils preserved in limestones can offer important insights into the taphonomy and paleoecology of these enigmatic organisms living on the eve of the Cambrian explosion.